2000
DOI: 10.1143/jjap.39.5875
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transmission, Photoluminescence, and Raman Scattering of Porous SiC Prepared from p-Type 6H SiC

Abstract: The optical transmission, temperature-dependence of the photoluminescence (PL), and Raman scattering of porous SiC prepared from p-type 6H-SiC are compared with those from bulk p-type 6H-SiC. While the transmission spectrum of bulk SiC at room temperature reveals a relatively sharp edge corresponding to its band gap at 3.03 eV, the transmission edge of porous SiC (PSC) is too wide to determine its band gap. It is believed that this wide edge might be due to surface states in PSC. At room temperature, the PL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…4(b), the transmittance of porous samples has been significantly decreased compared to the flat sample, especially for samples c and d. After anodic etching, the porous 6H-SiC layers are still crystalline and they should be transparent for the wavelength above bandgap. However, the observed low transmittance performance of porous 6H-SiC sample is attributable to the enormous surface states [4]. …”
Section: Reflectance and Transmittance In Porous 6h-sicmentioning
confidence: 95%
See 3 more Smart Citations
“…4(b), the transmittance of porous samples has been significantly decreased compared to the flat sample, especially for samples c and d. After anodic etching, the porous 6H-SiC layers are still crystalline and they should be transparent for the wavelength above bandgap. However, the observed low transmittance performance of porous 6H-SiC sample is attributable to the enormous surface states [4]. …”
Section: Reflectance and Transmittance In Porous 6h-sicmentioning
confidence: 95%
“…Porous SiC is a potentially attractive material for light emitting diodes (LEDs), photodetectors, sensors and substrate for monocrystalline SiC epitaxy [1][2][3][4]. Among these applications, porous SiC has potential to realize fluorescent SiC based white LEDs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We describe characteristic luminescence from n-type SiC during porous etching in the dark under breakdown conditions. Matsumoto et al, 7 Petrovakoch et al, 8 and Kim et al 9 reported a strong enhancement of the roomtemperature photoluminescence from porous n-type 6H-SiC. Kim et al also noted an increase in emitted intensity for EL.…”
mentioning
confidence: 94%